Nature-inspired antimicrobial nanofibers for infection control - Mayandi, Venkatesh (Nanyang Technological University, 2021)
There is a growing demand for durable advanced wound dressings for the management of persistent infections after deep burn injuries. In my thesis, we have designed antibiotic free durable prototype wound dressings by taking advantage of strong interfacial interactions between gelatin (Gel) and epsilon-poly-L-lysine (εPL) and their bio-inspired polydopamine (pDA) crosslinking using ammonium carbonate diffusion method (εPL_Gel_pDA). The εPL_Gel_pDA dressings displayed broad spectrum antimicrobial properties against Gram-positive, Gram-negative and yeast strains. The dressing’s material revealed excellent biocompatibility and cell proliferative properties for both human dermal fibroblasts (hDFs) and immortalized human keratinocytes (HaCaT). In vivo wound healing properties of the dressings were examined in both un-infected, Staphylococcus aureus and Pseudomonas aeruginosa colonized partial- thickness burns of porcine model. In the uninfected burn injury model, the εPL_Gel_pDA mats displayed higher wound closure compared to commercially available silver-based dressings. In the infected burns, εPL_Gel_pDA mats leads to increased wound closure, helps in significant reduction in the bacterial bioburden (>4 log 10 reduction), higher keratinization and faster re-epithelialization when compared to placebo and Aquacel®Ag. Overall, this thesis identified the combined utility of bio- inspired crosslinker, biocompatible antiseptic polymer and εPL_Gel_pDA nanofibers as advanced prototype wound dressings and established its superiority over commercial silver-based dressings. These prototype wound dressings that we developed are beneficial in reducing bacterial colonization and infection, decreasing the dressing change frequency and thus reducing the related pain and nursing cost, helps in absorbing excess exudates and maintaining the wound bed moist. This is a potentially valuable approach for treating life-threatening burn injuries and burn-related infections.